Performance analysis of combined transmit-SC - Thoen, S. (IEEE Transactions on communications)
The average bit-error rate of transmit antenna selection combined with receive maximum-ratio combining is computed as a function of the transmit antenna update rate when using binary phase-shift keying in flat Rayleigh fading channels. This scheme achieves an order of diversity equal to the product of the number of transmit and receive antennas. Therefore, it can gain significant diversity benefits over traditional receive diversity schemes by distributing the antennas over the transmit and receive side